Konsep Dasar Belajar di SDIT Cendikia - Nurhaeniah Nurhaeniah; Nurul Maspupah (AS-SABIQUN, 2020)
The purpose of this study is to find out the meaning of learrning, this study uses a qualitative approach, tjhen the instruments used are observation and documention of learning activities in class.the results of the analysis of student learning are obtained i the cognitive shutter which is the value of student evaluations when working on evaluation questions given by the teacher when the learning process takes place. The results of this study can be used SDIT CENDIKIA to find out learning styles of student learning outcomes and can be used for consideration of schools and parents of students, especially those in grades V and VI.